2017
DOI: 10.1371/journal.pone.0175084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of frequency on fretting wear behavior of Ti/TiN multilayer film on depleted uranium

Abstract: The Ti/TiN multi-layer film was prepared on the depleted uranium (DU) substrate by cathodic arc ion plating equipment. The character of multi-layer film was studied by SEM, XRD and AES, revealed that the surface was composed of small compact particle and the cross-section had a multi-layer structure. The fretting wear performance under different frequencies was performed by a MFT-6000 machine with a ball-on-plate configuration. The wear morphology was analyzed by white light interferometer, OM and SEM with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The substrate material did not emerge on the surface, which indicated that the multilayer film was not worn out. From the EDS spectra [ 26 ], at the center of the wear scars, the dominant elements were Ti and N, with a low content of O and Fe. At the edge of the wear scar, the content of Fe and O increased with the decrease of the content of Ti and N. Ti and N appeared in a “W” shape, indicating that the Ti/TiN multilayer film wear was much more severe at the edges than in the center.…”
Section: Resultsmentioning
confidence: 99%
“…The substrate material did not emerge on the surface, which indicated that the multilayer film was not worn out. From the EDS spectra [ 26 ], at the center of the wear scars, the dominant elements were Ti and N, with a low content of O and Fe. At the edge of the wear scar, the content of Fe and O increased with the decrease of the content of Ti and N. Ti and N appeared in a “W” shape, indicating that the Ti/TiN multilayer film wear was much more severe at the edges than in the center.…”
Section: Resultsmentioning
confidence: 99%
“…Although the micron-level fretting wear and contact of rubber materials were rarely reported, studies on ceramics and metals have been extensively developed. Mindlin [ 14 ] proposed that there were slip regions and non-slip regions in the fretting contact area under certain conditions and analyzed the fretting stress distribution on the contact surface. Waterhouse [ 15 ] divided the fretting process into three stages: initial, oxidation and steady states.…”
Section: Introductionmentioning
confidence: 99%
“…Ding et al [ 22 ] showed that the partial slip region was always associated with slight wear, the mixed region formed cracks, and the gross slip region mainly produced wear and damage of materials. A lot of studies showed that there were many influencing factors on the fretting wear behavior of materials, including frequency [ 23 , 24 ], normal force [ 25 , 26 ], displacement amplitude [ 27 , 28 ], and even temperature [ 29 , 30 ], surface roughness and so on [ 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%